On Research Integrity within Science Training - Almeida, Maria Strecht; Almeida, Maria Rosário (Journal of Academic Writing, 2025)
Here we report a teaching practice exploring integrity issues related to the use of images in scientific and/or academic writing or, more broadly, in communication. The practice is intended to raise students’ awareness of the need of complying with research integrity principles/norms. It is targeted at undergraduate students in the molecular biosciences, more specifically, to students enrolled in a First Degree in Biochemistry course. It has been implemented in the context of a course unit in which the students perform laboratory work – within a small project – usually originating data that is reported as graphs or as pictures in their laboratory reports. These visual representations are also normally used in articles published in scientific peer-reviewed journals. We implemented a group assignment based on the analysis of guidelines of different journals regarding the preparation of figures, including acceptable image processing and manipulation, as well as on the application of these guidelines on both written and oral reports. We could observe that the students performed the proposed activity with commitment and interest in the aspects explored. Moreover, the exercise improved their critical thinking ability as demonstrated through in-class discussions. In the present work, we discuss challenges of including illustrations in scientific texts in view of science teaching.